The use of isobutyl alcohol for methacrylate synthesis - Zhyznevskiy, Vyacheslav; Gumenetskiy, Volodymyr; Shyshchak, Olena; Fedevych, Yevhen (Publishing House of Lviv Polytechnic National University, 2011)
Methyl methacrylates synthesis via oxidative conversion of isobutyl alcohol has been investigated in accordance with different schemes. The possibility of its use as an alternative raw material instead of isobutylene and tert-butyl alcohol has been established. Using the scheme isobutyl alcohol ® methacrylonitrile ® methyl methacrylate the product with ultimate yield of 64.8 % has been obtained. Taking into consideration the recirculation of unreacted methacrolein the yield is 81.9 %. This scheme may be recommended for industrial application. Досліджено синтез метилметакрилатів окиснювальним перетворенням ізобутилового спирту за різними схемами. Встановлена можливість використання його як вихідної альтернативної сировини ізобутилену та трет.бутиловому спирту. При одержанні метилметакрилатів за схемою: ізобутиловий спирт ® метакрилонітрил ® метилметакрилат одержано продукт, сумарний вихід якого на поданий спирт дорівнює 64,8 %, а з рециркуляцією непрореагованого метакролеїну - 81,9 %. Цю схему можна рекомендувати для впровадження в промисловість.
Використання ізобутилового спирту для синтезу метакрилатів
Keywords: oxidation; oxidative amonolysis; catalyst; methacrylonitrile; methyl methacrylate; окиснення; окиснювальний амоноліз; каталізатор; метакрилонітрил; метилметакрилат